Association Between Dietary Zinc Intake and Metabolic Syndrome. A Meta-Analysis of Observational Studies - Ding, Jun; Liu, Qi; Liu, Ze; Guo, Hongbin; Liang, Jieyu; Zhang, Yi (Frontiers in Nutrition, 2022)
Background: Epidemiological studies have investigated the association between dietary zinc intake and metabolic syndrome (MetS). However, their results are conflicting. This meta-analysis was therefore employed to investigate the associations further. Methods: A comprehensive literature search was employed by using the electronic database of PubMed, Web of Science and Embase up to November 2021. The pooled relative risk (RR) of MetS for the highest versus lowest dietary zinc intake category, and the weighted mean difference (WMD) of dietary zinc intake for MetS versus control subjects as well as their corresponding 95% confidence interval (CI) were calculated. Results: A total of 13 observational studies (18073 participants) were identified in this meta-analysis. The overall multi-variable adjusted RR demonstrated that the dietary zinc intake was inversely associated with MetS (RR=0.75, 95%CI: 0.61 to 0.93; P=0.009). The subgroup analysis confirmed such findings in cross-sectional (RR=0.70, 95%CI: 0.55 to 0.87; P=0.002), NCEP-ATP III (RR=0.64, 95%CI: 0.48 to 0.84; P=0.002), adult (RR=0.77, 95%CI: 0.62 to 0.96; P=0.02), dietary recall method (RR=0.70, 95%CI: 0.55 to 0.87; P=0.002) and >500 sample-sized study (RR=0.79, 95%CI: 0.64 to 0.99; P=0.002), respectively. On the other hand, the overall combined WMD showed that the dietary zinc intake in MetS was also lower than that in control subjects (WMD=-0.21, 95%CI: -0.42 to 0.00; P=0.05). Conclusions: Our results suggest that the dietary zinc intake is negatively associated with MetS. However, due to the limitation of available evidence. More well-designed prospective cohort studies are still needed.